ANALISIS KESESUAIAN UNIT BISNIS TERHADAP PERUSAHAAN KORPORAT DENGAN MENGGUNAKAN CORPORATE PARENTING FRAMEWORK - , Imam Budhi Susanto, S. E, John Suprihanto, Drs, MIM, Ph D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
According to Thompson & Strickland (2001), a company commits diversification just to increase the company value for the benefit of their shareholders. In order to do so, diversified companies have to achieve a better performance compared with each business unit performance if they stand alone (stand alone enterprises). Several ways could be taken when the company decided to diversify its business. One of them is by doing mergers and acquisitions. However, acquisition also has the potential for failure. Problems that are often found is difficulties in integration. Synergy occurs when assets are used together to produce greater value when compared with the use of separately by each company. To achieve synergies, companies should be able to identify the level of balance between business units with the company corporate. One method that can be used to identify this is by using corporate parenting framework (Goold, et al. 1995). This framework uses a structured analysis approach (structured analytical approach) which consists of four main components to assess the level of conformity that is described in parenting fit matrix, namely Critical success factors, Parenting opportunity, characteristic Parenting, and Parenting fit matrix. Mapping business unit on parenting fit matrix will describe the business unit's position in the corporate portfolio into 5 main categories, namely Heartland Business, Edge of Heartland Business, Business Ballast, Alien Territory Business, and Business Value Trap, where each position has implications for strategies that different for future development. After completing the identification, weighting and scoring process between business units and parent company, found that the score for variable critical success factors amounted to 4.0 and the score for variable parenting opportunites is 4.0. If the number is in describing the parenting fit into the matrix, it will show that the company was in territori edge of Heartland. Optimizing the benefits of which are owned by corporate companies, retain talent you have, and continue to develop competitive products and innovative is the miraculous way that can be done to win the competition.